An improved bicubic imaging fitting algorithm for 3D radar detection target - Fan-Ruo Li; Feng Yang; Rui Yan; Qiao Xu; Yi-Jin Li; Hong-Jia Xing (Applied Geophysics, 2022)

Currents shaped the genetic structure of Tridentiger barbatus (Günther 1861) along the Chinese coast - Jiehong Wei; Min-Yun Liu; Jen-Chieh Shiao; Fan Li; Jinquan Yang; Yoshiyuki Iizuka; Bin Kang; Ruo-Shan Tseng; Huan-Jie Shao; Te-Yu Liao (Frontiers in Marine Science, 2022)
The modern coast of China is characterized by complicated hydrology, which might be a potential factor shaping genetic structure of marine organisms. Tridentiger barbatus is a widespread benthic goby in coastal China whose range expansion might depend on larval dispersal in its spawning season. We explored the genetic structure of T. barbatus and its interrelationships with coastal currents, planktonic larval duration, and Pleistocene climate fluctuations. Genealogies of Cytb , Rh , and RAG1 reveal two lineages in T. barbatus , namely the southern and northern lineages. The southern lineage is distributed through the South China Sea to the South Yellow Sea but is absent from the North Yellow Sea and Bohai Sea. The HYCOM average flow field indicates an eddy between the North and South Yellow Seas, which might cause larval retention and limit dispersal of the southern lineage into the North Yellow Sea and the Bohai Sea. The northern lineage is distributed through the South Yellow Sea to the Bohai Sea but is absent from the South China Sea and East China Sea. The distribution of the northern lineage fits the eastward deflection of the Yellow Sea Coastal Current at the boundary of the East China Sea and South Yellow Sea, which might limit southward larval dispersal of the northern lineage into the East China Sea. We also uncovered two Cytb haplotype groups within the southern lineage, namely groups A and B, whose distributions might be shaped by the northward Taiwan Strait Current. The coincidence between the genetic structure of T. barbatus and the coastal currents and eddies strongly implies significant roles of larval dispersal and current transportation in shaping the genetic structure of T. barbatus . In addition, significant isolation by distance is found in the southern lineage, which coincides with its short planktonic larval duration (20–30 days). The inference on divergence time suggests that the observed lineages and haplotype groups in T. barbatus originated in the Pleistocene glaciations. Therefore, the coastal currents, planktonic larval duration, and historical glacial isolation are proposed as important factors shaping the genetic structure of T. barbatus .

Genomic characterization of a new enamovirus infecting common bean - Ruo-bin Lu; Ping-xiu Lan; Ru-jing Kang; Guan-lin Tan; Xiao-jiao Chen; Ruhui Li; Fan Li (Archives of Virology, 2022)

Effect of Sodium Salicylate on Calcium Currents and Exocytosis in Cochlear Inner Hair Cells: Implications for Tinnitus Generation - Ting Fan; Meng-Ya Xiang; Ruo-Qiao Zhou; Wen Li; Li-Qin Wang; Peng-Fei Guan; Geng-Lin Li; Yun-Feng Wang; Jian Li (Neuroscience Bulletin, 2022)